2015
DOI: 10.1002/ajp.22479
|View full text |Cite
|
Sign up to set email alerts
|

From frugivore to folivore: Altitudinal variations in the diet and feeding ecology of the Bioko Island drill (Mandrillus leucophaeus poensis)

Abstract: Variation in the quality and availability of food resources can greatly influence the ecology, behavior, and conservation of wild primates. We studied the influence of altitudinal differences in resource availability on diet in wild drill monkeys (Mandrillus leucophaeus poensis) on Bioko Island, Equatorial Guinea. We compared fecal samples (n = 234) collected across three consecutive dry seasons for drills living in lowland (0-300 m asl) forest with nearby (18 km distance) drills living in montane forest (500-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 79 publications
0
6
1
Order By: Relevance
“…These results differ from previous findings, where mandrills increase their herb consumption when fruits are scarce (Hoshino 1985;Tutin et al 1997), and may imply within-species variation in feeding strategy, as observed in drills on Bioko Island (Owens et al 2015). Herbs and woody tissue are both low-quality foods, which are common alternative foods for largesized monkeys (Hemingway and Bynum 2005).…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…These results differ from previous findings, where mandrills increase their herb consumption when fruits are scarce (Hoshino 1985;Tutin et al 1997), and may imply within-species variation in feeding strategy, as observed in drills on Bioko Island (Owens et al 2015). Herbs and woody tissue are both low-quality foods, which are common alternative foods for largesized monkeys (Hemingway and Bynum 2005).…”
Section: Discussioncontrasting
confidence: 94%
“…The effects of seasonal inundation and steepness on the capture rates were unclear. These habitat parameters may not affect mandrill habitat use: in central Gabon, mandrills are observed in forests close to streams frequently (Lahm 1986), and drills range in montane forests with steep altitudinal gradients (Owens et al 2015;Wild et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specialized woolly lemurs, however, show decreased densities at the more disturbed site (97). Several fairly large-bodied primate folivores appear to have highly flexible diets and incorporate a high proportion of fruit when available (90,98,99). Notably, frugo-folivores show greater variation in habitat size and patchiness, indicating potential greater tolerance for habitat disturbance, than either frugivores or folivores (100).…”
Section: Discussionmentioning
confidence: 99%
“…Every month we monitored the availability of plant resources at both sites. Using randomly chosen transects, we quantified the number of trees and lianas bearing fruits (Sutherland, 2006 andOwens et al, 2015). In the 14-ha fragment, we used four 250 m × 10 m transects (monthly area sampled: 1 ha), while in the 522-ha fragment, we used two pre-existing 750 m × 10 m transects (monthly area sampled = 1.5 ha).…”
Section: Food Availability Estimatesmentioning
confidence: 99%